Shifting Operators in Geometric Quantization - Richard Cushman; Jędrzej Śniatycki (Axioms, 2020)
The original Bohr-Sommerfeld theory of quantization did not give operators of transitions between quantum quantum states. This paper derives these operators, using the first principles of geometric quantization.